The validity of rapid test to detect prostate-specific antigen (PSA) in seminal fluid (Faculty of Medicine Universitas Indonesia, 2011)
Background: This study was conducted to determine whether the rapid test device can be used to detect PSA in seminal fluid specifically, for solving sexual assault cases. Methods: A cross sectional study has been conducted. A total of 45 samples were taken consecutively. Semen was diluted in serially up to 1:5.000.000 and male urin up to 1:200 using distilled water, whereas female urin was not diluted. Samples were analyzed using rapid test PSA. Results: The proportion of positive results of PSA in seminal fluid, male urin and female urin respectively was 100%, 6.67%, and 0%. Statistically, these differences are highly significant. The analysis revealed that the PSA rapid test device was 100% sensitive and 96.67% specific to detect seminal fluid. The test also have PPV 93.75%, NPV 100%, LR(+) 33.33, LR(-) 0, and AUC 0.983. Conclusion: PSA Rapid Test is very specific and sensitive to detect PSA in seminal fluid. Therefore, this device is suggested for forensic use in sexual assault cases. (Med J Indones 2011; 20:278-82)